Optical Response of UV Laser Irradiated Extrinsic Semiconductor - Maryam Sardar; Zaka Ullah; Anwar Latif; Bushra Jabar; Abida Perveen; Muhammad Shahid Rafique; Muhammad Khaleeq-Ur-Rahman; Laser and Optronics Centre, Department of Physics, University of Engineering & Technology, Lahore - 54890, Pakistan
Fine polished samples of p-silicon were irradiated in ambient air using Excimer Laser and Spectroscopic Ellipsometry was employed to investigate their various optical properties. The changes in optical constants (refractive index and extinction coefficient) and optical band gap energy were noticed in incident wavelength range 500–1000 nm. Both refractive index and extinction coefficient decrease exponentially before and after irradiation. A fall in the optical band gap energy of p-silicon was also observed after laser exposure, which makes the materials suitable for variety of optoelectronics applications.
Keywords: Physics; Optics; Electronics; radiowave and microwave technology; direct energy conversion and storage